Evaluación de un recubrimiento de quitosano obtenido de Aspergillus niger en una forma farmacéutica de liberación modificada (FLM) (2024)
Chitosan (QN) is a naturally occurring, biodegradable, and biocompatible polysaccharide. It has shown great versatility in the pharmaceutical field due to its various characteristics. QN is commonly extracted from crustaceans, but other sources exist, such as the mycelium of filamentous fungi (e.g., Aspergillus niger). This study aimed to evaluate chitosan obtained from A. niger as a coating for a modified-release pharmaceutical dosage form (MRDF). To achieve this, 3 QN extractions were performed from A. niger mycelium. The obtained QN samples were analyzed for the degree of deacetylation (%DDA) by potentiometric titration and were characterized by Infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC). The %DDA values for extractions #1, #2, and #3 were 48.23 %, 48.32 %, 41.99 %, 39.30 %, 39.71 %, 39.64 %, 39.82 %, 48.21 %. QN from extraction #3 with an average %DDA of 41.34 % was selected to coat tablets. Five formulations were prepared, varying the polymer concentration, vehicle, and the addition of modulating excipients. It was observed that formulations with alcoholic vehicle and excipients showed better spraying. The coated tablets were subjected to a dissolution test, which showed rapid tablet disintegration and coating release. This was due to the partial coating of the tablets. It was concluded that the obtained material corresponds to chitosan, but a greater amount of coating is required to ensure modified release.